Stress-induced anxiety-related behavior in mice is driven by enhanced excitability of ventral tegmental area GABA neurons - Mitten, Eric H.; Souders, Anna; Marron Fernandez de Velasco, Ezequiel; Wickman, Kevin (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Stress and trauma are significant risk factors for many neuropsychiatric disorders and diseases, including anxiety disorders. Stress-induced anxiety symptoms have been attributed to enhanced excitability in circuits controlling fear, anxiety, and aversion. A growing body of evidence has implicated GABAergic neurons of the ventral tegmental area (VTA) in aversion processing and affective behavior.We used an unpredictable footshock (uFS) model, together with electrophysiological and behavioral approaches, to investigate the role of VTA GABA neurons in anxiety-related behavior in mice.Results: One day after a single uFS session, C57BL/6J mice exhibited elevated anxiety-related behavior and VTA GABA neuron excitability. The enhanced excitability of VTA GABA neurons was correlated with increased glutamatergic input and a reduction in postsynaptic signaling mediated via GABAA and GABAB receptors. Chemogenetic activation of VTA GABA neurons was sufficient to increase anxiety-related behavior in stress-naïve mice. In addition, chemogenetic inhibition of VTA GABA neurons suppressed anxiety-related behavior in mice exposed to uFS.Discussion: These data show that VTA GABA neurons are an early substrate for stress-induced anxiety-related behavior in mice and suggest that approaches mitigating enhanced excitability of VTA GABA neurons may hold promise for the treatment of anxiety provoked by stress and trauma.